Health-Care Seeking Pathways Of Psychiatry Patients In North Karnataka of India - A Hospital-Based: Exploratory Cross-Sectional Study - Alinawaz Khan; Narayan R Mutalik; Harish Kulkarni; Manjula R (University Library System, University of Pittsburgh, 2022)
INTRODUCTION: Neuropsychiatric disorders contribute for 13% of the total morbidities globally. In 2017, a study revealed that 14% of the Indian Population suffered from psychiatric health problems. The WHO estimates 2443 DALYs (Disability adjusted life years) per 100000 population in India due to psychiatric problems.  The non-availability of mental health services, stigma, and superstitions associated with mental disorders, along with the unwillingness or inability of families to care for their mentally ill relatives, appear to be major cause behind delay in approaching a psychiatrist. These factors act as major barriers in the pathways of care for these patients, thereby increasing the unmet need. An understanding of the way people seek care for mental disorders is important for implementing mental health services, and developing effective referral mechanisms. Hence this study was taken up with the objectives. OBJECTIVEs: To determine health-care seeking pathways of psychiatry patients using WHO pathways of care proforma and to explore the social and cultural determinants of health-care seeking behaviour in them. METHODOLOGY: This exploratory cross-sectional study includes newly diagnosed psychiatry patients (ICD-10), visiting psychiatry OPD  in a private medical college in Bagalkot, North Karnataka,  India. Sample size for proportion was calculated to be 340 ~350, taking 33% as P (Pilot study) and at 5% absolute precision at 95% confidence level.  Written Informed consent were obtained from the study participants or from the patient attenders, in case of inability to give informed consent.  Predesigned and pretested proforma were used for obtaining socio-demographic details of subjects. Patients were examined and diagnosed by the Psychiatrist (Principal Investigator). World Health Organisation (WHO) pathways to care proforma were used to obtain the health-care seeking behaviour of these study subjects. Statistical analysis will be done using SPSS software version19 and appropriate statistical tests will be applied. RESULTS: In the pilot study, we observed that about 32% of patients firstly approached medical practitioners, followed by psychiatrists and faith healers. An average delay of 24 months was found in reaching psychiatric services. CONCLUSIONS: There is a substantial delay in health-care seeking of psychiatry patients to psychiatrist, as per the pilot study. Further completion of this study is required to understand the extent of the problem, and socio-cultural factors leading to such delay. Generating awareness among the general public to address cultural myths and stigma related to psychiatric illnesses is required